HUBUNGAN KUALITAS PELAYANAN BELLBOY DENGAN KEPUASAN TAMU DI HOTEL ROCKY PLAZA PADANG - Wasisto, Fapenta; Kasmita, Kasmita; Abrian, Youmil (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The purpose of this study are: (1) Describe the quality of service bellboy at the Hotel Rocky Plaza Padang, (2) to describe the satisfaction of the guests at the Hotel Rocky Plaza Padang and (3) analyze the relationship between service quality with guest satisfaction bellboy at the Hotel Rocky Plaza Padang. This type of research is correlational. The population is all guests who stayed at Rocky Plaza Hotel Padang. The method used is non propability insedental sampling technique sampling with a sample of 98 people. The data collection is done by using a questionnaire that has been tested for validity and reliability, then the data were analyzed by descriptive and correlation productmoment using the computer program SPSS version 16:00 The results showed that: (1) Quality of service bellboy are in the very good category (97%), (2) Guest Satisfaction are in the very good category (96%) and (3) There is a relationship that is positive and significant correlation between quality of service bellboy with guest satisfaction with the r value of 0.570 (sig 0.000) with a strong interpretation. Keywords: Quality of Service Bellboy And Guest Satisfaction